The Causal Relationship Between the Exchange Rate and the Inflation Rate in Algeria During the Period 1990-2023 - Amel Touer; Omeyr Cheloufi (Dirassat Journal Economic Issue, 2025)
This study aims to investigate the causal relationship between the exchange rate and the inflation rate in Algeria, during the period extending from 1990-2023, using the VAR model, the short-term Granger causality test, and the Toda Yamamoto test in the long term. The results of the study concluded that there is a single causal relationship from the exchange rate. To the inflation rate in the short term and its sustainability in the long term. This result is consistent with economic theory, which indicates that high inflation rates were mainly caused by the decline in the value of the currency.